THE SOCIAL IMAGINARY WORLD OF EXTREME ADVENTURERS: A STUDY OF ANNAPURNA (Fiep Bulletin - online, 2015)
We see the growth of various sports practices involving adventure and risk, also known as radical or adventure sports, whose most common scenario is nature. The paradox is that this fascination for uncertainty, emptiness and the unexpected emerges among individuals of modern societies that value safety, enclosure and the obligations of residence. This post-modern change in behavior, whose supreme value is the “desire for liberty”, results in a world lived as uncertain, uncontrollable and frightening (Guiddens, 1991; Bauman, 1998; Lyotard, 2002; Maffesoli, 2003; Lipovetsky, 2004). The present study aims to comprehend the meanings that the adventure of climbing acquires in the imaginary universe of nine climbers on their first climb to a peak more than 8,000 meters high. The study has a qualitative nature and an interpretive character. The sampling was made up of the discourses of nine climbers, on their first expedition to the Annapurna peak in the Himalayas, which originated the book by the same name. The discourse analysis of Orlandi (2000, 2001) was used. The linguistic marks that emerged from the discourses permitted an explanation of the meanings  sacrifice, contemplation, anthropomorphosis of the mountains, body limitation, facing the adversary and ecstasy  in their multiple senses. We conclude that living on the limit to which these few brave souls subjected themselves would perhaps mean death, but to these ultra-human beings, an abode is found in that which is extreme. The unforeseeable and uncontrolled goes hand in hand with athletes, challenging them. They sought to enlist themselves in immortality. The imaginary world is heroic, solar (Durand, 1989).
Keywords: Social Imaginary; Body; Adventure Sports; Climbing.